Christopher McIntosh, Gardens of the Gods: Myth, Magic, and Meaning - Smoley, Richard (Pomegranate, 2007)
Christopher McIntosh, Gardens of the Gods: Myth, Magic, and Meaning (London: I.B. Tauris & Co., 2005), 203 pp., 22.95 (paper).